Assessment of dialysis initiation by a fuzzy mathematics equation (ADIFE): a study protocol for a randomised controlled trial. Issue 9 (8th September 2019) - Chen, Jilin; Liu, Ying; Chen, Xiangmei; Sun, Xuefeng; Li, Wei; Yang, Wang; Li, Ping; Sun, Ximing; Wang, Degang; Jiang, Hongli; Shi, Wei; Liu, Wenhu; et al.
Abstract : Introduction: Starting dialysis early or late both result in a low quality of life and a poor prognosis in patients undergoing haemodialysis. However, there remains no consensus on the optimal timing of dialysis initiation, mainly because of a lack of suitable methods to assess variations in dialysis initiation time. We have established a novel equation named DIFE (Dialysis Initiation based on Fuzzy-mathematics Equation) through a retrospective, multicentre clinical cohort study in China to determine the most suitable timing of dialysis initiation. The predictors of the DIFE include nine biochemical markers and clinical variables that together influence dialysis initiation. To externally validate the clinical accuracy of DIFE, we designed the assessment of DIFE (ADIFE) study as a prospective, open-label, multicentre, randomised controlled trial to assess the clinical outcomes among patients who initiate dialysis in an optimal start dialysis group and a late-start dialysis group, based on DIFE. Methods and analysis: A total of 388 enrolled patients with end-stage renal disease will be randomised 1:1 to the optimal start dialysis group, with a DIFE value between 30 and 35, or the late-start dialysis group, with a DIFE value less than 30, using the Randomization and Trial Supply Management system. Participants will be assessed for changes in signs and symptoms, dialysis mode and parameters, biochemical and inflammatory markers, Subjective Global Assessment, Kidney Disease Quality of Life Short Form, Cognitive Assessment, medical costs, adverse events and concomitant medication at baseline, predialysis visiting stage and postdialysis visiting stage, every 12–24 weeks. The following data will be recorded on standardised online electronic case report forms. The primary endpoint is 3-year all-cause mortality. The secondary endpoints include non-fatal cerebrocardiovascular events, annual hospitalisation rate, quality of life, medical costs and haemodialysis related complications. Ethics and dissemination: Ethical approval was obtained from the Ethics Committee of the First Affiliated Hospital of Dalian Medical University China (registration no: YJ-KY-2017–119) and the ethics committees of all participating centres. The final results of the ADIFE trial will be presented to the study sponsor, clinical researchers and the patient and public involvement reference group. Findings will be disseminated through peer-reviewed journals, Clinical Practice Guidelines and at scientific meetings. Trial registration number: ClinicalTrial.gov. Registry (NCT03385902 ); pre-results.